Final answer:
To solve the quadratic equation 3x² + 5x - 2 = 0, we can use the quadratic formula. The solutions to the equation are x = -2/3 or x = 1.
Step-by-step explanation:
To solve the quadratic equation 3x² + 5x - 2 = 0, we can use the quadratic formula. The quadratic formula states that for an equation of the form ax² + bx + c = 0, the solutions for x can be found using the formula:
x = (-b ± √(b² - 4ac)) / (2a)
For our equation, a = 3, b = 5, and c = -2. Plugging in these values, we get:
x = (-5 ± √(5² - 4(3)(-2))) / (2(3))
Simplifying further, we have:
x = (-5 ± √(25 + 24)) / 6
x = (-5 ± √49) / 6
x = (-5 ± 7) / 6
Therefore, the solutions to the equation are:
x = -2/3 or x = 1